Architectural Technical Debt in Embedded Systems. Issue 1 (13th September 2016) - Martini, Antonio; Bosch, Jan
Abstract: The introduction of Agile Software Development in large companies developing embedded systems aims at shortening the time‐to‐market for new business value for the customers. However, evidences show how system engineering needs to be integrated in the process in order to avoid the degradation of architectural system qualities. Such phenomenon has recently been identified with a financial metaphor, Architectural Technical Debt, which maps sub‐optimal architectural solutions to taking a debt, and its costly impact into an interest to be paid in the long term. Through a multiple case study in 5 companies, we show what are the current practical challenges related to the long‐term accumulation of Architectural Technical Debt, and how system engineers need to track and manage such phenomenon in order to avoid costly impact such as development crises and costly re‐design.